Ремінісценція з нарису Льва Толстого в повісті Тараса Шевченка - Боронь, О.В. (Слово і Час, 2019)
У статті доведено, що Шевченкова згадка у повісті “Прогулка с удовольствием и не без морали” про четвертий бастіон під час оборони Севастополя у Кримській війні походить із нарису Льва Толстого “Севастополь в декабре месяце”, про що висловлювалися припущення і раніше. Автор статті розглядає обізнаність Шевченка із творчістю Толстого, аналізуючи наявність у лектурі українського письменника тих чи тих номерів журналів, у яких друкувалися твори російського прозаїка. Завдяки ремінісценції з нарису Толстого Шевченко збагатив власний виклад додатковими асоціаціями, звільнивши себе від необхідності вдаватися до розлогих описів і пояснень. The paper attempts to prove that Shevchenko’s remark in the story “A Walk with Pleasure and Not Without Some Moral” about the fourth bastion during the defense of Sevastopol in the Crimean War derives from the essay by Leo Tolstoy “Sevastopol in December”, as it has been already supposed earlier. The author of the paper focuses on Shevchenko’s awareness of the works by Tolstoy investigating if the Russian magazines in which the works of the Russian prose writer were printed belonged to the reading scope of the Ukrainian writer. As L. Khinkulov’s version saying that the publication of “The Tale of the Sorrow-Evil” in the journal “Sovremennik” (1856, No. 3) served as the source of Shevchenko’s series “Parable of the Prodigal Son” has been reasonably rejected, the Ukrainian poet’s awareness of the story by Tolstoy “Snowstorm” printed in the same issue may be considered only as hypothetical. L. Bolshakov's statement that Shevchenko, while writing the story, drew the material from the direct participants of the Crimean War is denied: when he met them in Astrakhan in 1857, the first version of the work had been already written. The publication of the essay by Tolstoy in the newspaper “Russkiy invalid” also could not be the source of the reminiscence, as it contained only the first part where the bastion was not discussed. The author of the paper comes to the conclusion that the epithet ‘strashnyi’ (‘terrible’), used twice in Shevchenko’s story (the second time – in the comparative degree) and at least 4 times in different forms in the essay by Tolstoy, is the key to connecting Shevchenko's phrase with the essay “Sevastopol in December”. According to the researcher, this word came into the poet’s mind while reading the essay in “Sovremennik” and association emerged when he mentioned the fourth bastion in his story. Shevchenko thus enriched his own narration with additional associations and semantic overtones, freeing himself from the need of using detailed descriptions and explanations.